Rotating machinery, vibro-acoustics & laser vibrometry. proceedings of the 36th IMAC, a conference and exposition on structural dynamics 2018 /: proceedings of the 36th IMAC, a conference and exposition on structural dynamics 2018. Volume 7 : (2018) - Unknown
No abstract available